The Art of Phenomena Construction: A Framework for Coming Up with Research Phenomena beyond ‘the Usual Suspects’ - Alvesson, Mats; Sandberg, Jörgen (Journal of management studies, 2024)
Despite the centrality of research phenomena, the process of their definition is often neglected and reduced to a simple choosing of pre‐established subjects of interest. However, good research not only includes empirical work aimed at more or less ‘given as fact’ phenomena. It also involves phenomena construction: that is, the process of generating and establishing phenomena to investigate and theorize. We contend that phenomena construction is not separate from, but integral to, both the empirical and theorizing phases in research. As few phenomena are truly ‘given’ or straightforward to observe, good research calls for careful and creative construction of the phenomenon under investigation. We propose and elaborate a framework that enables researchers to generate and establish research phenomena beyond those currently available in their specific area of interest and, based on this, to produce more imaginative and impactful research.